Pengaruh Pengungkapan Akuntansi Lingkungan dan Mekanisme Good Corporate Governance Terhadap Nilai Perusahaan - Yulianti, Selvi; Rezky Amalya, Wulan (DINASTI RESEARCH, 2024)
The purpose of this study is to assess the impact of environmental accounting disclosure and Good Corporate Governance (GCG) processes on firm value in pharmaceutical businesses listed on the Indonesia Stock Exchange (IDX) between 2021 and 2023. The context of this study is the rising recognition of the significance of sustainability and good governance in the pharmaceutical business following the epidemic. This research employs a quantitative approach, focusing on both descriptive and causal analyses. Data were collected from pharmaceutical firms' annual reports and evaluated using multiple linear regression. The findings reveal that environmental accounting disclosure has a considerable impact on business value, but the GCG method has no meaningful effect. The study concludes that investments in sustainable environmental initiatives significantly enhance business value, though further improvement in GCG practices is necessary to maximize its impact.